Las chivas turísticas y las actividades recreativas en el cantón Quevedo - Herrera Yaguana, Malu Stefany (2022)
Tourism development has become an important source of economic resources, jobs, new businesses, taxes, transportation mobility. Ecuador has shown a sustained effort to promote its tourism development in the different natural landscapes of its territory. Among the tourist products offered by Cantón Quevedo, are the tourist goats, the aquatic goats and other varied recreational activities that can be developed in the tourist context. The role that tourist chivas and recreational activities can play in the tourism and economic development of the canton is a necessary topic to develop. An exploratory investigation was proposed because the phenomenon has its own elements generated in its historical and cultural context. To understand the scope and importance of the subject studied, the opinion of several experts attached to the Delphi method was considered and to proceed with the scientific inquiry, qualitative research was used and the techniques used were the consultation of scientific sources and a specific survey elaborated to the investigation.